2011
DOI: 10.1002/jez.b.21417
|View full text |Cite
|
Sign up to set email alerts
|

Animal egg as evolutionary innovation: a solution to the “embryonic hourglass” puzzle

Abstract: The evolutionary origin of the egg stage of animal development presents several difficulties for conventional developmental and evolutionary narratives. If the egg's internal organization represents a template for key features of the developed organism, why can taxa within a given phylum exhibit very different egg types, pass through a common intermediate morphology (the so-called "phylotypic stage"), only to diverge again, thus exemplifying the embryonic "hourglass"? Moreover, if different egg types typically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 113 publications
(142 reference statements)
1
32
0
Order By: Relevance
“…Arenicola and Nereis) are not closer to each other in the parameter space than to the patterns of other, more phylogenetically distant, species. This suggests that the underlying developmental parameters are relatively easy to change ( presumably a small number of mutational changes are required) (Newman, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Arenicola and Nereis) are not closer to each other in the parameter space than to the patterns of other, more phylogenetically distant, species. This suggests that the underlying developmental parameters are relatively easy to change ( presumably a small number of mutational changes are required) (Newman, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Even though the DPM framework proposed by Newman and Bhat (Newman and Bhat, 2009;Newman, 2011) is in principle applicable to all multicellular organisms, plant development has features that suggest the presence of additional or different sets of DPMs and perhaps even a different DPM-GRN relationship. In particular, we note that many plants are characterized by having open, indeterminate development during which new tissues and organs are added continuously over the course of their life times.…”
Section: Characteristics Of Plant Development and Organizationmentioning
confidence: 99%
“…Because DPMs only come into play in animal embryos when a critical number of cells have been generated (e.g., at the morula or blastula stage), it has been suggested that disparate autonomous patterning processes that may occur in the eggs of subphylum taxa serve mainly to set the initial and boundary conditions for DPM implementation, with conservation of DPM-determined "phylotypic" body plans (Newman, 2011). However, because of the immobility of plant cells, an autonomous patterning mechanism like FCW would be expected to have more profound consequences for plant body plan organization, placing it more in the DPM category.…”
Section: Future Cell Wall (Fcw)mentioning
confidence: 99%
See 2 more Smart Citations